Analisis Faktor-Faktor yang Mempengaruhi Kesejahteraan Ekonomi Mustahik Melalui Pemberdayaan Zakat (Studi Kasus PenyaluranZakat Produktif/ Modal Usaha pada Bazda Kota Jambi) - Mutia, Agustina; Zahara, Anzu Elvia (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2009)
The efficiency of zakat for productive activities has a strong Islamic basic, although in Alquran is not explicitly stated so, but there is afreedom in managing the way to use it whether for consumptive or productive activities. The perceptions in society especially for small trader in Jambi got zakat for productive activities is very satisfying. The leading of zakat which has been done by Bazda Jambi could increase the living level or the income for that small trader (Mustahik).